2019
DOI: 10.1242/dmm.039578
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of tumor hepatocytes to normal hepatocytes during liver tumor regression in an oncogene-expressing transgenic zebrafish model

Abstract: Tumors are frequently dependent on primary oncogenes to maintain their malignant properties (known as ‘oncogene addiction’). We have previously established several inducible hepatocellular carcinoma (HCC) models in zebrafish by transgenic expression of an oncogene. These tumor models are strongly oncogene addicted, as the induced and histologically proven liver tumors regress after suppression of oncogene expression by removal of a chemical inducer. However, the question of whether the liver tumor cells are el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Thus we consider liver after tumor regression as a model of a «new» evolving organ. Such consideration is supported by a recent publication [31] that showed reversion of tumor hepatocytes to normal hepatocytes, although with somewhat different properties, during liver tumor regression in an oncogene transgenic zebrafish model. That is why we performed a study of expression of evolutionary novel genes in transgenic zebrafish tumors after their regression in experimental conditions.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Thus we consider liver after tumor regression as a model of a «new» evolving organ. Such consideration is supported by a recent publication [31] that showed reversion of tumor hepatocytes to normal hepatocytes, although with somewhat different properties, during liver tumor regression in an oncogene transgenic zebrafish model. That is why we performed a study of expression of evolutionary novel genes in transgenic zebrafish tumors after their regression in experimental conditions.…”
Section: Discussionmentioning
confidence: 83%
“…In the recent paper of Li et al, [31] the authors have shown that after reversion of tumor hepatocytes to normal hepatocytes during liver tumor regression in an oncogene transgenic zebrafish model, some tumor signaling pathways remain activated in tumor-reverted hepatocytes, according to transcriptomes analysis. This is in accordance with the data obtained in the present article.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Still more intriguing is the action of retinoic acid, which was initially demonstrated to promote reversion of teratocarcinoma [168], has been later recognized to induce a nearly complete differentiation of leukemogenic cells in acute promyelocytic leukemia through the induction of terminal differentiation into granulocytes [169], thus reversing cell fate from cancer to healthy fully differentiated state, which can, in turn, lead to partial or complete clinical remission. Recently [170], such a cell fate reversion was also observed for a solid tumour. The most recent achievement, the conversion of breast invasive cancer cells into adipocytes, was shown in a mouse model while using PPAR-gamma (member of nuclear receptors regulating adipocyte differentiation) agonist combined with the MEK inhibitor [171].…”
Section: Reprogramming Of Positional Information Can Be Used For Cancmentioning
confidence: 80%
“…There are two possible mechanisms of tumour regression: (1) tumour hepatocytes undergo cell death and are eliminated while normal hepatocytes eventually replace these tumour hepatocytes via proliferation and differentiation, and (2) tumour hepatocytes might be directly reverted to normal hepatocytes. In order to test the two possibilities, we developed a CreER transgenic line that allowed us to trace liver cell lineage (Figure 1F) [82]. In this transgenic line, tamoxifen-activated Cre protein, CreER T2 , is expressed only in the presence of doxycycline.…”
Section: Oncogene Addiction: Tumour Regression and Re-inductionmentioning
confidence: 99%